Regional and social disparities in cessation behavior and motivation to quit among U.S. adult current smokers, Tobacco Use Supplement to the U.S. Census Bureau's Current Population Survey 2014–15 and 2018–19 - Johnson, Candon; Martinez, Jose (Frontiers in Public Health, 2024)
Introduction Variation in smoking cessation behaviors and motivators across the United States may contribute to health disparities. This study investigates regional differences over time in two key cessation motivators (quit interest and doctor's advice to quit) and two cessation behaviors (past-year quit attempts and recent successful cessation) across diverse demographic factors. Methods Data were analyzed from two releases of the Tobacco Use Supplement to the U.S. Census Bureau's Current Population Survey (TUS-CPS) for the years 2014–15 and 2018–19. The analysis included sex, age, race and ethnicity, education, marital status, employment status, and household income. Results Findings from 2018 to 2019 TUS-CPS revealed that quit interest was highest in the Northeast and lowest in the Midwest, while doctor's advice to quit was most prevalent in the Northeast and least in the West. Past-year quit attempts were most common in the Northeast and least in the South. Recent successful cessation (defined as quitting for 6 to 12 months) was highest in the Northeast and Midwest, with the South showing the lowest rates. Compared to the 2014–15 survey, 14 demographic groups (7 in the Midwest, 6 in the South, and 1 in the West) showed decreases in both quit interest and actions to quit. Notably, the Asian non-Hispanic group in the Northeast experienced a significant decrease in quit interest (–17.9%) but an increase in recent successful cessation (+369.2%). Discussion Overall, the study indicates that while quit interest was highest in the West, the South exhibited the lowest rates of quit attempts and successful cessation. Significant differences were also noted between age groups. These findings highlight the need for further research into cessation behaviors at more granular levels to inform policies aimed at reducing smoking-related health disparities among populations facing the greatest challenges in cessation.